The effectiveness of e-ID card services in subdistrict city North Ternate - Ibrahim, Abdulhalil Hi.; Deni, Saiful; Saraha, Syofyan; Taher, Sofyan Bin; Wance, Marno (International research journal of management, IT and social sciences, 2021)
This research is a descriptive qualitative study to analyze or explain the effectiveness of e-ID services in Ternate City District Office in improving the handling of service of e-ID; study descriptive aimed to explain something the object of research is relatively deep and focused on the object study. The research results show that the implementation of e-ID services in the District of North Ternate City began recording the mass until manually recording is currently not implemented effectively. This can be proven by several indicators of effectiveness measurement, namely the Achievement of Objectives in terms of the time target has not been achieved. In terms of the final goal, which is the concrete target of recording implementation for compulsory e-ID Card, only 92.49% have been recorded while the remaining 7.51 % have not been recorded. There is miscommunication between the sub-district government and the civil registry office of Ternate City so that for now, all recordings have been pulled in the civil registry office of Ternate City.